Functions of the press: Journalists' study 1973 - Fjaestad, Björn; Holmlöv, Per Gunnar (Handelshögskolan i Stockholm, 1982)
This study is part of the research program 'The Role of the Press in Society', a project initiated by the 1972 Commission of the Press. The survey deals with four major questions. Firstly the journalists´ goals with the newspaper and their own work, i.e. the newspaper´s tasks in society. Secondly to what extent these tasks are fulfilled. Thirdly, if there are differences between ideal and reality, which are the factors that prevent or make it difficult to reach the goals. Finally the survey deals with different ways to change the press for better fulfilment of the tasks.

Forskningsprojektet "Pressens funktioner" genomfördes på uppdrag av 1972 års pressutredning. Projektets centrala frågeställning rörde vilken roll pressen har i samhället: för individer, grupper och institutioner, samt pressens roll i sammanhang med övriga massmedier. Av speciellt intresse var massmedias förmedling av information och opinioner. Begreppet massmedia begränsas till dagspress, populärpress, organisationspress och radio-TV, med huvudvikt på dagspress och tidskriftspress.
Pressens funktioner: Journaliststudien 1973
Keywords: Media; Media; Working conditions; Arbetsförhållanden; Social Sciences; Samhällsvetenskap